Treatment of rosacea with upadacitinib and abrocitinib: case report and review of evidence for Janus kinase inhibition in rosacea - Zhang, Ting; Liu, Xu; Zhang, Lu; Jiang, Xian (Frontiers in Immunology, 2024)
Introduction Conventional rosacea treatments are not uniformly pervasive, and the adverse reactions can potentially constrain their utility. The clinical use of JAK1 inhibitors upadacitinib and abrocitinib in the treatment of refractory rosacea has rarely been explored. Case report We presented two cases of patients who received the JAK1 inhibitor upadacitinib and four cases of patients who received the JAK1 inhibitor abrocitinib for the treatment of refractory rosacea. Discussion The JAK1 inhibitors upadacitinib and abrocitinib may be promising medical options for patients with refractory rosacea. However, the long-term safety and efficacy of upadacitinib and abrocitinib require prospective controlled studies to assess them more comprehensively.